Role of the Father of the Baby on Maternal Mental Health and Birth Outcomes Among Black Women in the United States. Issue 5 (September 2018) - N/A
Abstract : Understanding the role of the father of the baby in birth outcomes will provide the foundation for designing interventions to eliminate disparities in preterm birth among Black women. Our guest editor of this special topics series on the role of the father of the baby in maternal mental health and birth outcomes among Black women in the United States, Dr. Carmen Giurgescu, discusses the four featured articles and their potential contributions.